Perubahan Makanan Tradisional Arsik dalam Kemasan Modern - Josua Boyke William Jawak (Journal of Mandalika Literature, 2024)
The shift in consumer behavior patterns has led to changes in the packaging of traditional foods. Packaging, which was once solely a container to protect food, has now also become a means of attracting consumers. Food industry entrepreneurs play a role in this transformation, sparking a trend in the packaging of traditional foods. This change is driven by the market demand for traditional foods. Arsik, a traditional Batak dish, has also followed this trend of evolving packaging. This shift allows arsik to reach a broader market and present a more appealing appearance compared to traditional packaging. The use of aluminum foil packaging, zip sealers, and labels featuring a blend of images, gorga motifs, and colors that harmonize with the appearance of arsik gives it a modern packaging style. The modernization of arsik’s packaging is influenced by factors such as the form of its spices and environmental conditions. The impact of this packaging transformation also affects cultural, economic, and environmental aspects.